Hubungan Kepuasan Pelayanan KB Suntik dengan Minat menjadi Akseptor Tetap di BPM Mustardiyah - Nurhidayah Nurhidayah; Emy Ismiaty (Journal of Ners and Midwifery, 2016)
The cause of drop out in using injection contraceptionn caused by the couple factor, want to have more children, health factor and method of contraception that is the side effectand the cost. Besides, another factors that influence the choosing of contraception variation is education level knowledge, family prosperity, religion and support of husband and wife. Those factors will be influenced with the success of birth control program. The goal of this research was to identify the correlation of satificationof birth controlprogram by injection with the enthusiasm to be acceptor in BPM Mustardiyah Manyaran, Banyakan Kabupaten Kediri. The research was correlational and used crossectional approach. The variable of this research was the satification as independent variable and prosperity as dependent variable. The population were all of Birth control acceptor as much as 108 respondents. The sample 52 respondents by simple random sampling. The data analysis used chi quadrat. The result showed that 34 mothers (65,4%) in category of satisfy, and 35 mothers (67,3 %) was enthusiasm to be acceptor from. The analysis of the two variables showed that ï² value < ï¡ = 0,000 < 0,05 HÂ¹ accepted, means that there was correlation between birth controlsatisficationand enthusiasm to be acceptor in BPM MustardiyahManyaran, Banyakan Kabupaten Kediri. It was suggested for midwife to increase their knowledge to make their service better.